En præstekarriere: Om Vilh. Hansen, præst i Nykøbing Mors 1879-1926 - Trock, Carl (Kirkehistoriske Samlinger, 1994)
Hans Vilhelm Hansen (he called himself Vilh. Hansen) was vicar in the town of Nykøbing Mors from 1879 to 1926. He had hardly planned to remain in the position for the rest of his life when he started. But when the elective congregation at Mors in 1883 was excluded from the National Church he felt obliged to support the free congregation - also because he wanted to prevent it from going into wild opposition to the National Church. The many Grundtvigian vicars at Mors had looked up to the elective congregation as the ecclesiastical center of the island. This fact combined with ambitious lay leaders in the congregation, who both in church matters and politically were in strong opposition to the authorities, had contributed to the rupture together with the formalism of the church authorities. The rupture meant that the congregation stressed its affinity to the National Church rather than opposition towards it. The bishop, however, ordered the vicars of the island to keep away from the free congregation. Vilh. Hansen ignored the order and notified the bishop that he did so in order to prevent the free congregation and the National Church from drifting apart. The bishop did not understand him but believed that this really was the motive for for his disobedience. In 1887 the position as first vicar in Nykøbing became vacant and hesitantly Vilh. Hansen applied. The bishop wrote on his application to the Ministry that although Vilh. Hansen was gifted and active in his work he was unable to recommend his promotion since Vilh. Hansen did not find it wrong to support the free congregation and communicate there. In a letter to the Ministry the majority of the churchgoers had expressed the wish to have Vilh. Hansen as the first vicar. It did not help: a younger man was appointed. That passing over made a great commotion and was interpreted as if the Minister of Culture slighted a political opponent although Vilh. Hansen had held back in the political opposition. In an official denial he wrote that the case had been solved on the basis of principle concerning the position of the free congregation to the National Church. Vilh. Hansen remained in Nykøbing and gradually became the main support of the free congregation among the now few Grundtvigian vicars at Mors. In 1897 the first vicarage of the town became vacant again. Vilh. Hansen applied once more and was now appointed. It indicates a change in attitude of the bishop of the diocese both towards Vilh. Hansen and the free congregation. 1901 brought a change of political system. In Aalborg there was a Grundtvigian bishop. He was transferred in 1905 and when asked by the minister he expressed the wish that Vilh. Hansen succeeded him, but Vilh. Hansen declined. In 1908 he became dean of Mors. In 1912 the most prestigious Danish bishopric was to be filled. The Grundtvigian minister of culture offered the bishopric of Zealand to Vilh. Hansen. Again he declined - and remained another 14 years in Nykøbing as a popular vicar and respected dean. He did not experience that the free congregation as an elective congregation again became part of the National Church. But more than anybody else Vilh. Hansen had contributed to the fact that the strong tensions that could be felt even in the 1890’es were replaced by a more quiet ecclesiastical coexistence at Mors.